LEGAL PROTECTION OF ULAYAT RIGHTS - Lubis, Ramiah; Safithri, Hijriyana (Universitas Islam Negeri Raden Fatah Palembang, 2021)
Land is the surface of the earth which is one of the objects regulated by Agrarian Law. The new Agrarian Law must comply with the legal awareness of the people at large. Because the Indonesian people are largely subject to customary law, the new agrarian law will also be based on the provisions of customary law as original law, which are refined and adjusted to the interests of the community. Customary law is the main source in the formulation of national land laws, as the first source. In the land law, the hierarchy of land tenure rights is regulated, including the Ulayat Rights. The method used in this research is field research. Writing this research aims to describe the application of the distribution of customary land rights owned by the customary law community of the MuaraEnim district, namely Paya Angus Village and the form of legal protection for the indigenous people of Paya Angus, but because their work does not reside in Paya Angus Village. The result of this research is that the residents of Paya Angus village have obtained their customary rights in accordance with the regulations in force in the village and the form of legal protection obtained by the residents of Paya Angus village who live outside the village because they work in MuaraEnim district is not clearly explained about There is a legal basis and rules that regulate, but customary rights are recognized by law and its application refers to the Basic Agrarian Law and customary law in force in Paya Angus Village so that with an agreement from the village head, the community is still entitled to get rights. Ulayat and obliged to continuously cultivate the land